Development of Discovery Learning Assisted by Cabri Express Teaching Materials to Improve Students' Communication Ability and Mathematical Disposition - Risman Firmansyah; Asep Ikin Sugandi; Euis Eti Rohaeti (IKIP Siliwangi, 2023)
The purpose of this study was to improve students' mathematical concepts through improving communication skills and students' mathematical dispositions using Discovery Learning assisted by Cabri Express. This research is development research using the 4-D development model, which consists of the Define, Design, Develop, and Disseminate phases. The subjects in this study were 18 students. Data collection techniques in this study used the instrument questions given in the form of written tests, while the data analysis techniques in this study were data collection, data processing, data presentation, and concluding. So that the conclusions that can be drawn from this study are Cabri Express assisted teaching materials on flat plane material developed using three stages, namely define, design, and develop. Teaching materials have been validated with an average value of 87.3% with very valid and very practical criteria. Thus, the Cabri Express-assisted Discovery Learning teaching material on flat-sided spatial construction material is feasible to use. Furthermore, the teaching materials developed received a positive response from students with a percentage of 76% in the